Investigations of inorganic and organic fouling behaviors, antifouling and cleaning strategies for pressure retarded osmosis (PRO) membrane using seawater desalination brine and wastewater. (15th October 2016) - Han, Gang; Zhou, Jieliang; Wan, Chunfeng; Yang, Tianshi; Chung, Tai-Shung
Abstract: By employing seawater desalination brine (SWBr) and wastewater brine (WWBr) as the feed pair, membrane fouling behaviors as well as antifouling and cleaning strategies for the state-of-the-art thin-film composite polyethersulfone (TFC-PES) hollow fiber membrane have been systematically investigated under pressure retarded osmosis (PRO) operations. Fouling on the polyamide selective layer induced by the SWBr draw solution is relatively mild because of the outstanding membrane rejection and the hydration antifouling layer formed by the permeating water. However, using WWBr as the feed causes fast and severe internal concentration polarization (ICP) and fouling within the porous PES substrate, which result in dramatic flux and power density declines. In addition, the PRO fouling upon and within the porous substrate is highly irreversible. Experimental data show that both anti-scalant pretreatment and pH adjustment of WWBr could effectively mitigate inorganic fouling, while increasing feed flow velocity along the substrate surface is ineffective for fouling control. To clean the fouled membranes, hydraulic-pressure induced backwash and flushing with alkaline and NaOCl solutions on the fouled surface are effective strategies to remove foulants and regenerate membranes with a flux recovery of 83–90%. However, osmotic backwash shows low cleaning efficiency in PRO. In summary, a proper combination of feed pretreatment and membrane cleaning strategies has been demonstrated in this study to sustain PRO operations with a high water flux and power density. Graphical abstract: Highlights: Investigation of fouling behaviors, antifouling and cleaning strategies for TFC-PRO membrane. Real seawater desalination brine and wastewater were used as the draw and feed solutions. Fouling on the polyamide selective layer induced by seawater desalination brine is negligible. ICP and fouling caused by wastewater feed within the substrate are fast and significant. Proper pretreatment and cleaning strategies can effectively mitigate fouling and recover flux.